Prognostic Implication of the Absolute Lymphocyte to Absolute Monocyte Count Ratio in Patients With Classical Hodgkin Lymphoma Treated With Doxorubicin, Bleomycin, Vinblastine, and Dacarbazine or Equivalent Regimens. (26th February 2016) - Vassilakopoulos, Theodoros P.; Dimopoulou, Maria N.; Angelopoulou, Maria K.; Petevi, Kyriaki; Pangalis, Gerassimos A.; Moschogiannis, Maria; Dimou, Maria; Boutsikas, George; Kanellopoulos, Alexandros; Gainaru, Gabriella; Plata, Eleni; Flevari, Pagona; et al.
Abstract: Low absolute lymphocyte count (ALC) to absolute monocyte count (AMC) ratio (ALC/AMC) is an independent prognostic factor in Hodgkin lymphoma (HL), but different cutoffs (1.1, 1.5, and 2.9) have been applied. We aimed to validate the prognostic significance of ALC/AMC in 537 homogenously treated (doxorubicin, bleomycin, vinblastine, and dacarbazine or equivalents ± radiotherapy) classical HL patients at various cutoffs. The median ALC/AMC was 2.24 (0.44–20.50). The median AMC was 0.653 × 10 9 /L (0.050–2.070). Lower ALC/AMC was associated with established markers of adverse prognosis. In total, 477 (89%), 418 (78%), and 189 (35%) patients had an ALC/AMC ratio of ≥1.1, ≥1.5, and ≥2.9; respectively; 20% had monocytosis (≥0.9 × 10 9 /L). Ten-year time to progression (TTP) was 77% versus 55% for patients with ALC/AMC ≥1.1 and <1.1 ( p = .0002), 76% versus 68% for ALC/AMC ≥1.5 and <1.5 ( p = .049), 77% versus 73% for ALC/AMC ≥2.9 and <2.9 ( p = .35), and 79% versus 70% for ALC/AMC ≥2.24 and <2.24 ( p = .08), respectively. In stages ΙΑ/ΙΙΑ and in patients ≥60 years old, ALC/AMC had no significant effect on TTP. In advanced stages, ALC/AMC was significant only at the cutoff of 1.1 (10-year TTP 67% vs. 48%; p = .016). In younger, advanced-stage patients, the differences were more pronounced. In multivariate analysis of TTP, ALC/AMC < 1.1 ( p = .007) and stage IV ( p < .001) were independent prognostic factors; ALC/AMC was independent of International Prognostic Score in another model. ALC/AMC was more predictive of overall survival than TTP. At the cutoff of 1.1, ALC/AMC had independent prognostic value in multivariate analysis. However, the prognostically inferior group comprised only 11% of patients. Further research is needed prior to the widespread use of this promising marker. Abstract : Low absolute lymphocyte count (ALC) to absolute monocyte count (AMC) ratio is an independent prognostic factor in Hodgkin lymphoma (HL), but different cutoffs have been applied. It was found that at a cutoff of 1.1, ALC/AMC had independent prognostic value in multivariate analysis. Its prognostic significance appears stronger in advanced stages.